A Comprehensive Investigation on the Influence of Zeolite, Pumice, and Limestone Powder on the Characteristics of Eco-Friendly Calcium Aluminate Cement Mixes - A. R. Rasekhi Sahneh; M. A. Dashti Rahmatabadi; H. Madani; H. Dehghan Manshadi (Advances in Materials Science and Engineering)
The current research aims to investigate the influence of pumice, zeolite, and limestone powder as supplementary cementitious materials (SCMs) on the characteristics of calcium aluminate cement (CAC) composites. For this purpose, SCMs were used in substitution levels of 5%, 15%, 25%, 40%, and 60% of CAC. The results indicate that the active SCMs had a great influence on enhancing the characteristics of the cement composites. For instance, the mixtures with 40% pumice and zeolite outperformed the plain mixture in the compressive strength test by about 45% and 90% at 90 days, respectively. At the age of 90 days, the rapid chloride migration coefficient for the optimal mixture of Z40 (containing 40% zeolite) was reduced by about 93%, and the electrical resistance was increased by about 70% in comparison to the age of 28 days; however, at the same ages, for the plain mixture, the rapid chloride migration coefficient was increased by about 74%, and the electrical resistance was decreased by about 60%. At the age of 90 days, the electrical resistivity of the Z40 mixture was 685% higher compared to the plain mixture. The results show that the high cost of CAC composite could be significantly lowered by utilizing SCMs. Moreover, using SCMs could significantly lower greenhouse gas emissions. In addition, the tests including the modulus of rupture, modulus of elasticity, permeable pore space, XRD, and microstructural analyses were also carried out to study the mechanical and durability properties. It must be mentioned that the effect of high dosages of pumice and zeolite on the durability properties of this type of cement has not been studied previously, which can be considered an innovation of this study. Furthermore, the obtained results could be beneficial to develop applications of CAC.